Beginning Scribus - White, Robert; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Beginning Scribus is the book you wish you’d read when you downloaded Scribus for the first time. Scribus is an award-winning page-layout program used by newspaper designers, magazine designers and those who want to do proper page layout but not pay for an expensive solution. It is free and Open Source, providing a useful alternative for those who cannot afford or choose not to use Adobe InDesign or QuarkXpress. Beginning Scribus provides you with the skills you will need in order to use this program productively. It demonstrates the techniques used by printers and publishers in order to create a range of layouts and effects, and it shows you how you can use these techniques to design everything from a flyer to a three-fold brochure. Using the latest Scribus release, Beginning Scribus takes you through the process of designing a magazine from start to finish and teaches you some of the tricks of professional page layout and design. The book also provides a definitive guide to desktop publishing using free, open source tools, such as GIMP for photo manipulation. Brings professional page layout design into the home for free. Introduces you to valuable desktop publishing skills. Shows you how to create CVs, newsletters, brochures, magazines and printed adverts just like a professional graphic designer.
1. Scribus Basics -- 2. Getting to Know the Workspace -- 3. Text Frames and Font Management -- 4. Working With Graphics -- 5. Working With Color -- 6. Exporting and Printing Your Documents -- 7. Working with GIMP 8. Automating Scribus -- 9. Magazine Design -- 10. Interactive PDFs.
Keywords: Computer programming; Computer graphics; Web Development; Computer Graphics